Carbon nanotube sponge 3D anodes for urine-powered microbial fuel cell. Issue 14 (18th July 2017) - Zhou, Yu; Hou, Junxian; Chen, Wenwen; Liu, Zhongliang
ABSTRACT: Urine-powered microbial fuel cells (UMFCs) can recover energy from urine, a typical constituent of urban wastewater. Three-dimensional (3D) structure is advantageous for improving the anode performance, especially using carbon nanotube (CNT), which has good biocompatibility. It is proposed in this paper to use 3D carbon nanotube sponge (3DCS), which has a proper size of pores as anodes for UMFCs. The maximum output voltage is as high as 231.89 mV, and the power density is 1.24 W m −3 (per anode volume). The results show that 3DCS is a good choice for fabricating 3D anode for UMFCs.